Indications and Outcome of Re-Exploration Laparotomy in Surgical Patients - Abdul Basit Samad; Hamna Khalid; Muhammad Salim Akhtar; Muhammad Khalid Siddique; Hatim Khalid; Muhammad Ahmad (Pakistan Armed Forces Medical Journal, 2026)
Objective: To evaluate indications and outcome of re-exploration laparotomy in surgical patients.Study Design: Analytical cross-sectional study.Place and Duration of Study: Combined Military Hospital (CMH), Rawalpindi, Pakistan, from Mar to Sep 2023Methodology: This study enrolled 40 patients, who had redo-laparotomy between March to September 2023. Patients who needed second abdominal exploration while they were in the hospital or who were readmitted within 60 days following the first surgery were the subject of this research. Systematic data collection was conducted on all patients, including demographic data, medical history, clinical examinations, tests, treatments, and on-going problems.Results: Enrolled study participants had a mean age of 49.13±10.94 years with 10.00% cases being elective and 75% being emergency with an average of 2.95±1.15 days between laparotomies. The average length of stay for those who were released from the hospital was 19.85±4.34 days, of whom, 85% needed to be transferred to critical care or high dependency units. With a rate of 22.5% (n=9), this study observed a statistically significant increase in mortality following re-exploration.Conclusion: Re-exploration laparotomy carries significant morbidity and mortality. The predominantly emergency nature of these procedures, combined with the prolonged hospital stays, underscores the gravity of conditions necessitating re-intervention.